Comprehensive Management of Massive Transfusion in Postpartum Hemorrhage Patients - Ananta Kahar, Liliriawati (Riviera Publishing, 2025)
Postpartum hemorrhage (PPH) is one of the leading causes of maternal morbidity and mortality worldwide. This condition can cause significant blood loss in a short period of time, requiring rapid and appropriate intervention to prevent fatal complications. A 30-year-old female patient came to the hospital with G0P1A0H1 with bleeding from the birth canal, currently 37-38 weeks pregnant. After examination, the patient was found to have suspected placenta previa accreta. During surgery, grade 3 placenta accreta was found to have infiltrated the urinary bladder, and a joint operation was performed with the urology department. Intraoperative bleeding was approximately 2000 cc, and during the operation, 4 units of whole blood, 2 units of PRC, 4 units of FFP, and 4 units of cryoprecipitate were administered. Intraoperative hemodynamics fluctuated. After the operation, the patient was transferred to the ICU for monitoring. Management of postpartum hemorrhage (PPH) is based on rapid diagnosis and immediate replacement of lost blood volume, as well as restoration of the blood's ability to carry oxygen. In addition, prompt medical and surgical measures to address the underlying cause of bleeding are essential to prevent further blood loss